Baẏaska śikshā o grāmonnaẏana (Paścimabaṅga Sāmagrika Añcala Unnaẏana Parshada, 1981)
Role of adult education in rural development papers of a seminar organized by the West Bengal Comprehensive Area Development Corporation.